1986
DOI: 10.1677/joe.0.1090035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the granule population of gonadotrophs of hypogonadal (hpg) and normal female mice associated with the priming effect of LH-releasing hormone in vitro

Abstract: Changes in the size and position of secretory granules in pituitary gonadotrophs have been studied in relationship to LH release and self-priming induced by LH-releasing hormone (LHRH) in pituitary glands from normal and hypogonadal (hpg) female mice. Hemipituitary glands were preincubated and then incubated for either 1 or 2 h in the absence or presence of LHRH (8.5 nmol/l). The glands were either processed for ultrastructural morphometry or homogenized for the determination of pituitary LH content. Morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
(40 reference statements)
3
20
0
Order By: Relevance
“…This possible priming mechanism may be facilitated through the actions of either oestrogen (Thomas & Clarke 1997), or GnRH (Lewis et al 1986). In this study, polarisation of the granular area was evident in a proportion of gonadotrophs throughout the oestrous cycle, but no differences in proportions of polarised cells were observed.…”
mentioning
confidence: 43%
“…This possible priming mechanism may be facilitated through the actions of either oestrogen (Thomas & Clarke 1997), or GnRH (Lewis et al 1986). In this study, polarisation of the granular area was evident in a proportion of gonadotrophs throughout the oestrous cycle, but no differences in proportions of polarised cells were observed.…”
mentioning
confidence: 43%
“…In oestrogen-primed rats, the secretion of luteinising hormone (LH) in response to gonadotrophin-releasing hormone (GnRH) increases with successive exposures to GnRH, a phenomenon that Fink (1995) called 'self-priming'. With Morris and others, Fink showed that between exposures to GnRH, there is a 'margination' of secretory granules in gonadotrophs: how much LH is secreted in response to GnRH depends on how many granules lie close to the plasma membraneand GnRH could trigger the relocation of granules to these sites (Lewis et al 1986). This depends on the mobilisation by GnRH of intracellular calcium stores, so Leng and Ludwig, knowing that the release of neurosecretory granules in response to electrical activity was likely to depend on those granules being close to the site of depolarisation-induced calcium entry, wondered if something similar was happening in the dendrites of magnocellular neurons.…”
Section: The Milk-ejection Reflexmentioning
confidence: 99%
“…The history of neuroendocrinology has been the subject of several reviews (Harris 1955, Guillemin 1967, 1978, 2011, Harris 1972, 1986, 1988, Charlton 2008. Friedgood (1936) and Hinsey (1937) were arguably the first to postulate formally that the anterior pituitary gland was controlled by substances liberated into the hypophysial portal vessels from nerve terminals in the median eminence.…”
Section: Brief Historymentioning
confidence: 99%
“…Ultrastructural studies have shown that GnRH selfpriming involves an increase in length and a change in the angle of the microfilaments in gonadotrophs as well as a migration of secretory granules towards the plasmalemma of the gonadotroph (Lewis et al 1985(Lewis et al , 1986Fig. 6).…”
Section: Mechanisms Involved In Gnrh Self-primingmentioning
confidence: 99%
See 1 more Smart Citation